DESKRIPSI KETERLAKSANAAN PEMBELAJARAN TEMATIK DIMASA PANDEMI PADA SISWA KELAS V SEKOLAH DASAR NEGERI 05 PONTIANAK UTARA - Tarigas, Emelia Christine; Kartono, Kartono; Pranata, Rio (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The research describes the implementation of the thematic learning process during the Covid-19 pandemic and the teacher's constraints on implementing the thematic learning process during the Covid-19 pandemic. This research uses a qualitative descriptive method approach. Research participants acted as data sources, namely class V B thematic teachers. The research instrument was a human instrument, namely researchers. Data collection techniques are interviews and documentation. The data analysis technique is the Miles And Huberman model. The results of the research show that the implementation of the thematic learning process during the Covid-19 pandemic was carried out by teachers with online distance learning for fifth grade students using the WhatsApp application that was going quite well. The implementation of the thematic learning process during the pandemic with online distance learning for fifth grade students of North Pontianak 05 Public Elementary School, namely, the teacher makes online lesson plans, prepares teaching materials/materials, the teacher uses the assignment method, the teacher approaches students, teacher readiness, availability of facilities and infrastructure is sufficient to support learning that is carried out online, in the form of evaluation in online learning. In the implementation of the thematic learning process during the pandemic, teachers also experienced problems, while the obstacles experienced by teachers in implementing the thematic learning process with online distance learning during the Covid-19 pandemic, namely, during the process of delivering material, learning, the process of interaction with students in the learning process, constraints during evaluation and learning objectives, and constraints when managing teaching materials.